Validated Spectrophotometric Assay of Cefepime Hydrochloride and Cefuroxime Sodium Using a Tetrazolium Salt - Marwa S. Elazazy; Abadalla A. Shalaby (E-Journal of Chemistry)
A simple, rapid and sensitive spectrophotometric method for the determination of micro amounts of cefepime hydrochloride and cefuroxime sodium is described. The method is based on reduction of 2,3,5-triphenyltetrazolium chloride (TTC) by the cited drugs in slightly alkaline medium leading to formation of a highly colored formazan derivative. Different variables affecting the color development were investigated and optimized. Absorbance measurements were made at 483 nm. Under the proposed conditions, this method is applicable over concentration range of 4–50 µg ml-1 with molar absorpitivities ranging from 5.208 x 103–1.217 x 104 L.mol-1.cm-1 and Sandell's sensitivities ranging from 1.007 x 10-3–2.727 x10-3 µg cm-2. The proposed method was successfully applied for analysis of the cited drugs in formulations and the recovery percentages ranged from 99.47 to 99.8%. The results obtained demonstrated that the proposed method is equally accurate, precise and reproducible as the reported methods thus it is recommended for quality control and routine analysis where time, cost effectiveness and high specificity of analytical techniques are of great importance.